Hubungan Kredit Terhadap Besarnya Pajak Penghasilan Pada PT. Bank SulutGo - Piayi, Victor Daniel; Manoppo, Wilfried S.; Tamengkel, Lucky F. (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
In this era of globalization banking world is a service industry that is very important in supporting the financing of development, as an institution investment financing and working capital and as a lack of funds. Ones of the banking products that help support the success of the business world and to help the community is a credit facility, the credit provided by the bank is one of the largest productive activities that contribute revenue to banks. Although the placement of interest on credit has a big role in contributing income to the bank, but keep in mind that credit products have the highest level of risk, for that bank is very careful in doing credit expansion. Research object is PT. Bank North Sulawesi go and the purpose of research is to know the relationship of credit to the amount of income tax on PT. Bank SulutGo. The method of data analysis used is the method of correlation analysis, which is used to measure the closeness of a relationship between variables and to test the relationship between variables. Statistical results show that credit with income tax has a very close relationship. Where if the income of the credit amount increases, then automatically the amount of income tax also increasesKeywords: Credit Income Against Income Tax